EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA WEB KAHOOT! MODE TIM UNTUK MENINGKATKAN MINAT BELAJAR IPAS KELAS V SD - Haninda Cahya Ramadhani; Deni Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning interest is a crucial factor in the success of the educational process. However, in several elementary schools, including SD Negeri Wates 02, students’ interest in learning, particularly in the subject of Natural and Social Sciences (IPAS) for Grade V, remains low. Students often feel bored, disengaged, and unmotivated, while teachers tend to rely on traditional lecture methods without incorporating interactive media. This study aimed to examine the effectiveness of the cooperative learning model Teams Games Tournament (TGT) supported by the Kahoot! web application in team mode in increasing students’ learning interest in IPAS. Employing a sequential explanatory mixed-method design, the study involved Grade V students from two different elementary schools, assigned to an experimental group and a control group. Quantitative data were collected through pretest and posttest and analyzed using independent sample t-test, Welch t-test, and one-sample t-test. Qualitative data were gathered through structured interviews and observations and analyzed thematically. The results showed that the TGT model with Kahoot! significantly improved students’ interest in learning, with a notable difference between the experimental and control groups (Sig. = 0.045), and the posttest average of the experimental class exceeding the effectiveness threshold (Sig. = 0.002). An increase of 6.14% in scores from pretest to posttest was observed. These findings were supported by qualitative data indicating that both teachers and students found the learning process more engaging, interactive, and enjoyable, fostering better understanding and active participation. Therefore, the TGT model supported by Kahoot! in team mode is proven to be an effective and innovative strategy to enhance students’ learning interest in IPAS at the elementary level.